Right-Wing Populism and Religion in Europe and the USA - Haynes, Jeffrey (Religions (Basel, Switzerland ), 2020)
The aim of this paper is to examine comparatively the growth and political effectiveness of right-wing populism in Western Europe, Central Europe, and the USA since 9/11. The focus is on such politicians’ vilification of Islam as a faith and Muslims as a people. The paper examines the following research question: how and why do right-wing populists in the USA and Europe use an ideological form of “Christianity”, known variously as “Christianism” or “Christian civilizationism”, to vilify Muslims and Islam? The political purpose seems obvious: to influence public perceptions and to win votes by questioning the desirability of Muslims in both the USA and Europe, claiming that Muslims’ religious and cultural attributes make them unacceptable as neighbors. As Muslims are not capable, so the argument goes, of assimilating to European or American norms, values, and behavior, then they must be excluded or strongly controlled for the benefit of nativist communities. Right-wing populists in both the USA and Europe pursue this strategy because they see it as chiming well with public opinion at a time of great uncertainty, instability, and insecurity.